Fractal‐based lightning model for shielding failure rate calculation of transmission lines. Issue 6 (1st September 2018) - Rahiminejad, Abolfazl; Vahidi, Behrooz
Abstract : In this study, performance of lightning shielding system of transmission lines is investigated by means of a new fractal‐based model of simulated lightning. A new lightning downward stepped leader based on fractal approach is introduced in this study. The zigzag movement of lightning downward leader as well as branching nature are simulated using the proposed model. Moreover, a new charge distribution is proposed for branched lightning channel. In addition, the branch fading during lightning downward movement is also simulated in order to simulate the lightning closer to reality. The proposed method is applied for calculating the striking distance for a transmission line and the results are compared with those of leader progression model and different models of electrogeometric model. Furthermore, the shielding failure rate of some practical structures obtained by the proposed method is compared with the field observations. The results are discussed and superiority of the proposed simulated lightning model is concluded.